Oxygen-induced p(3 x 1) reconstruction of the W(100) surface - SHVETS, IGOR; MURPHY, SHANE (My University, 2005)
The oxidation of the W(100) surface at elevated temperatures has been studied using room temperature STM and LEED. High exposure of the clean surface to O-2 at 1500 K followed by flash-annealing to 2300 K in UHV results in the formation of a novel p(3 x 1) reconstruction, which is imaged by STM as a missing-row structure on the surface. Upon further annealing in UHV, this surface develops a floreted LEED pattern characteristic of twinned microdomains of monoclinic WO., while maintaining the p(3 x 1) missing-row Structure. Atomically resolved STM images of this surface show a complex domain structure with single and double W < 010 > rows coexisting on the surface in different domains.
PUBLISHED
Keywords: STM; tungsten-oxide films; adsorption; oxidation; resonstruction; WO3(001); Atomic, molecular and chemical physics